2019
DOI: 10.2214/ajr.18.20392
|View full text |Cite|
|
Sign up to set email alerts
|

New Frontiers: An Update on Computer-Aided Diagnosis for Breast Imaging in the Age of Artificial Intelligence

Abstract: OBJECTIVE. The purpose of this article is to compare traditional versus machine learning–based computer-aided detection (CAD) platforms in breast imaging with a focus on mammography, to underscore limitations of traditional CAD, and to highlight potential solutions in new CAD systems under development for the future. CONCLUSION. CAD development for breast imaging is undergoing a paradigm shift based on vast improvement of computing power and rapid emergence of advanced deep learning algorithms, heralding new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 64 publications
0
62
0
Order By: Relevance
“…As a result, our model has the ability to learn both local features across the entire image as well as macroscopic features such as symmetry between breasts. For a more comprehensive review of prior work, refer to one of the recent reviews [ 33 ], [ 34 ].…”
Section: Related Workmentioning
confidence: 99%
“…As a result, our model has the ability to learn both local features across the entire image as well as macroscopic features such as symmetry between breasts. For a more comprehensive review of prior work, refer to one of the recent reviews [ 33 ], [ 34 ].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, a reliable computer-aided diagnosis (CAD) system is needed to help radiologists make a correct diagnosis. Related research has shown that the CAD system can effectively improve the diagnosis efficiency, reduces the rate of misdiagnosis and the burden of patients [4,5]. In many medical institutions, CAD systems has been used in clinical diagnosis as doctors' reference [6].…”
Section: Introductionmentioning
confidence: 99%
“…(77) The new deep learning-based techniques may reduce the false-positive rates and provide more accurate diagnoses. Computer-aided diagnosis has had a mixed track record in patient care, dampening enthusiasm for these technologies in clinical settings.…”
Section: Challenges In Implementationmentioning
confidence: 99%
“…Early CAD systems, which were FDA-approved and integrated into direct clinical patient care, predominantly for mammography, often had high sensitivities but also high false-positive rates, leading to inefficiencies and unnecessary testing in clinical practice. (77) The new deep learning-based techniques may reduce the false-positive rates and provide more accurate diagnoses. Another challenge to implementing these technologies in clinical settings has been practice workflow and economic factors.…”
Section: Challenges In Implementationmentioning
confidence: 99%